Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Classpoint terhadap Motivasi Belajar Siswa pada Pembelajaran Pendidikan Agama Kristen di Kelas Xi SMA Negeri 1 Sibolangit - Nurlina; Bangun Munthe; Bangun (Attractive : Innovative Education Journal, 2024)
The aim of this research is to determine the effect of using Classpoint-based interactive learning media on student learning motivation in Christian religious education learning in class XI of SMA Negeri 1 Sibolangit. This research uses descriptive quantitative methods, and the sampling technique used is simple random sampling with a sample size of 34 people. The data collection tool is a questionnaire in the form of multiple choices which has been carried out with instrument validation tests. After carrying out the Pearson product moment correlation statistical test. From the results of the correlation test, it was obtained (r) 0.63 with a determination test of 39.69% and to find out whether the correlation coefficient was significant or not at the level (a) = 0.05, a "t" test was carried out with the test criteria if t_count obtained from calculation is greater (>) than t_table at a significance level of 1-0.05 with dk=n-2 then the hypothesis is accepted and in other cases rejected. From the test results, t_count > t_table (4.58 > 1.69), so the hypothesis is accepted. Thus, a significant relationship can be found between the influence of using Classpoint-Based Interactive Learning Media on Student Learning Motivation in Christian Religious Education Learning in class XI of SMA Negeri 1 Sibolangit.